Exploring the causal relationship between female reproductive traits and frailty: a two-sample mendelian randomization study - Fan, Maoxia; Wang, Dandan; Wu, Xiaoqi; Gao, Wulin (Frontiers in Physiology, 2024)
The impact of female reproductive factors, including age at menarche (AAM), age at first birth (AFB), age at first sexual intercourse (AFS), age at natural menopause (ANM), and pregnancy abortion (PA), on the risk of developing frailty remains uncertain. Our objective is to examine the potential causal relationship between female reproductive traits and frailty through the utilization of two-sample univariable Mendelian Randomization (UVMR) and multivariable Mendelian Randomization (MVMR) analyses. Methods: Leveraging large-scale Genome Wide Association Study (GWAS) data from individuals of European ancestry, we performed two-sample UVMR and MVMR analyses to examine the causal relationship between female reproductive traits and frailty. The primary analysis employed inverse-variance-weighted (IVW) estimation, and sensitivity analyses were conducted to assess the robustness of the findings. Results: The UVMR analysis revealed a significant causal relationship between female reproductive traits (AFS, AFB, AAM) and frailty [IVW: OR=0.74, 95%CI(0.70~0.79), P=0.000; OR=0.93, 95%CI(0.92~0.95), P=0.000; OR=0.96, 95%CI(0.95~0.98), P=0.000]. However, there was no significant effect of ANM and PA on frailty (P > 0.05). The sensitivity analysis results were robust, supporting the findings. Furthermore, this association remained significant even after adjusting for body mass index (BMI) and educational attainment (EA) in the MVMR analysis [IVW: OR=0.94, 95%Cl(0.91~0.97), P=0.000; OR=0.77, 95%Cl(0.70~0.86), P=0.000; OR=0.95, 95%Cl(0.94~0.97), P=0.000]. BMI and EA serve as mediators in this process. Conclusion: Our research has established a significant causal relationship between female reproductive traits (AFS, AFB, AAM) and frailty, with BMI and EA acting as mediating factors in this process. However, further research is warranted to validate our findings and elucidate the underlying biological mechanisms.